The global politics of arms sales - Pierre, Andrew J. (Princeton University Press, 1982)
Marshaling a great deal of new information in a highly readable manner, the author explains the reasons for the dramatic expansion of arms sales during the past decade and clearly traces such trends as the rise in sophistication of weapons being sold so as to include the most advanced technologies, and the shift in sales to unstable parts of the Third World.